2020
DOI: 10.37358/rc.20.6.8203
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Iodides from Groundwater and Surface Water using an Optimized Ion Chromatographic Method

Abstract: The research aimed to provide an optimized method for the determination of iodides concentration in groundwater and surface water sources using ion chromatography technique. The analyses were conducted by using a conductivity detector, with a 35 mM KOH mobile phase, at a flow rate of 1 mL/min, the temperature in the detector chamber and the intensity of the suppressor current being set at 350C and 87 mA, respectively. The interferences given by other ions were also investigated, and the performance pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In Romania, groundwater from different sources were affected by pollution (some sources from Timis, Bihor, Arad, Covasna Counties), earlier studies reported As concentration in the range 11 µg/L to 1505 µg/L (Tudorache et al, 2011) The usual analytical methods for controlling As concentrations in water are Grafite Furnance Atomic Absorption Spectrometry (GF-AAS), Inductively Coupled Plasma Optical Emission Spectrometry with ultrasonic nebuliser (USN-ICP-OES), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), due to their high sensitivity, selectivity and wide range of linearity. In addition, electrochemical methods are considered easy to use due to the low cost, short analysis time, minimal pretreatment of the sample (Badescu et al, 2016). For the analysis of arsenic species, chromatographic techniques such as: highperformance liquid chromatography (HPLC), gas chromatography (GC) and capillary electrophoresis (CE), are generally coupled with AAS and ICP-MS detectors to simultaneously obtain a good separation and excellent sensitivity (Huimin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Romania, groundwater from different sources were affected by pollution (some sources from Timis, Bihor, Arad, Covasna Counties), earlier studies reported As concentration in the range 11 µg/L to 1505 µg/L (Tudorache et al, 2011) The usual analytical methods for controlling As concentrations in water are Grafite Furnance Atomic Absorption Spectrometry (GF-AAS), Inductively Coupled Plasma Optical Emission Spectrometry with ultrasonic nebuliser (USN-ICP-OES), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), due to their high sensitivity, selectivity and wide range of linearity. In addition, electrochemical methods are considered easy to use due to the low cost, short analysis time, minimal pretreatment of the sample (Badescu et al, 2016). For the analysis of arsenic species, chromatographic techniques such as: highperformance liquid chromatography (HPLC), gas chromatography (GC) and capillary electrophoresis (CE), are generally coupled with AAS and ICP-MS detectors to simultaneously obtain a good separation and excellent sensitivity (Huimin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%